Herbarium book: Learning media in medicinal plants lecture - Nining Nuraida; Suraida Suraida; Nurlinda Nurlinda; Try Susanti (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to (1) determine the types of medicinal plants used in Teluk Kayu Putih village, (2) describe the development of the herbarium book media for medicinal plants lecture, (3) determine the validity and (4) the readability test of the herbarium book of medicinal plants as a learning media. The ADDIE development model research consists of 2 stages of research. The first stage of qualitative research is to obtain data on the types of medicinal plants in Teluk Kayu Putih Village. The second stage of media development is making a herbarium book. Field data collection methods include observation and documentation (first stage) and questionnaire (second stage). The results obtained are: (1) The types of plants used as medicine in Teluk Kayu Putih Village are 27 species grouped into 25 families; the most plant species came from Family Euphorbiaceae, Myrtaceae, and Zingiberaceae, each with 2 species, (2) The media developed are specimens of medicinal plants originating from Teluk Kayu Putih village, including plant parts that have been dried using a pressing technique, arranged in a scrapbook with a black base color derived from black cardboard, the spesimens are pasted one by one and then identified, as well as put together and bound in a spiral to form a book, (3) The validity test from material experts and media experts on the media produced obtained a score of 81,35% and 85,26%, while the validity test score obtained a score of 86,31% (very feasible), (4) The readability test of the herbarium book by 23 respondents obtained an average percentage score of 92,6%, means that the media is suitable to use.